Compound C induces the ramification of murine microglia in an AMPK-independent and small rhogtpase-dependent manner. (7th September 2016) - Huang, C.; Lu, X.; Wang, J.L.; Tong, L.J.; Ling, Y.; Jiang, B.; Yang, R.R.; Zhang, W.
Highlights: Compound C (CC) induces a reversible ramification of microglia. CC-mediated microglial ramification is associated with inflammation inhibition. CC increases microglial BDNF expression and phagocytic activity. PI3K/Akt and ERK1/2 activation mediates the effect of CC on microglial ramification. Small RhoGTPase activation mediates the effect of CC on microglial ramification. Abstract: Microglial cells are the pivotal immune cells of the central nervous system. Adult microglia cells under physiological conditions are in a ramification state with extensively branched processes. Upon disease stimulation, they retract their processes and become activated. Induction of ramification is an attracting strategy to terminate the excessive activation of microglia. Here, we investigated the influence of compound C (CC) on microglial shape. Results showed that CC reversibly induced a ramification of murine microglia in both basal and inflammatory conditions. These pro-ramification effects were independent of adenosine 5′-monophosphate-activated protein kinase (AMPK) inhibition as both AMPKα1 and AMPKα2 silence failed to induce microglial ramification. The ramification state of microglia induced by CC was associated with a decrease in pro-inflammatory factors and an increase in brain-derived neurotrophic factors (BDNF) protein and phagocytic activity. Mechanistic studies confirmed that the phosphatidylinositol 3-kinase (PI3K)–protein kinase B (Akt) signal, extracellular signal-regulated kinase 1/2 (ERK1/2) or small RhoGTPase activation mediated the effect of CC on microglial shape change based on the following observations: (i) CC induced a significant activation of the small RhoGTPase Rac1 and Cdc42; (ii) CC promoted the phosphorylation of ERK1/2 and Akt; (iii) inhibition of Rac1, Cdc42, ERK1/2, or the PI3K–Akt signal abolished the effect of CC on microglial shape change. These signal mechanisms were also ascertained in primary microglia. Our results explore a potential agent that promotes microglial ramification, and provide an alternative explanation for the neuroprotective effects of CC in various disease models such as brain ischemia and subarachnoid hemorrhage.